From workshop to waste magnet : environmental inequality in the Philadelphia region - Sicotte, Diane, 1960- (Nature, society, and culture., 2016)
From Workshop to Waste Magnet presents Philadelphia's environmental history as a bracing case study in mismanagement and injustice. Tracing the complex interactions among economic decline, federal regulations, local politics, and shifting ethnic demographics, sociologist Diane Sicotte uncovers how only a few communities came to host many types of polluting or waste disposal land uses. What she finds reveals the devastation that occurs when mass quantities of society's wastes mix with toxic levels of systemic racism and inequality.